Design of Medan Fine Art Museum with the Application of Futuristic Architecture - N. Vinky Rahman; Rahmah Y.A. (Talenta Publisher, 2019)
The Futuristic architecture is a concept that illustrates the planning and development is not based on something related to the past, but try to describe the future. The futuristic architecture concept is applied to bring a new style to the building. The purpose is to eliminate the ancient impression on the building of the Fine Art Museum in Medan. The Medan Fine Arts Museum was designed as a recreation and education place to learn about fine art. Other than a place to store and preserve works of art, The Museum also provides a variety of facilities. The methodology of these projects starts with literature studies, site selection, site observation, and concept design. After carrying out these steps, the concept of space and the shape of the Museum building can be determined. Therefore, by designing this Medan Fine Art Museum with the application of Futuristic Architecture, it is hoped can increase the attractiveness of visitors and make an educative recreational place in Medan.